Collaborative optimal dispatch of microgrid and electric vehicles based on the Stackelberg game - Bo, Wen; Zhang, Wenqiang; Du, Rongyu; Wang, Donglai; Zhao, Yan; Li, Quanzheng; Zhang, Zhen (Frontiers in Energy Research, 2022)
The development of microgrid and electric vehicles has become an important part of the current energy layout. A useful complementary advantage can be formed between electric vehicles and microgrid. Consumers of microgrid and electric vehicles can absorb renewable energy and narrow the peak-valley difference of net load curve while ensuring their own pecuniary interests. Based on the idea of Stackelberg game, an optimal dispatching model of microgrid with electric vehicles is proposed, where the benefits of state of charge are taken into account. In the upper layer of the model, the charging and discharging behaviors of electric vehicles are guided with the minimum operating cost of microgrid as the goal. In the lower model, electric vehicle users adjust the charging and discharging strategies with the goal of maximizing their individual interests. The results demonstrate that the proposed model not only reflects the benefits of both the master and the slave, but also reduces the peak-valley difference of microgrid load. The charging and discharging time of electric vehicles are reduced, and the state of charge is maintained at a high level.